2020
DOI: 10.33448/rsd-v9i1.1609
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem matemática da cinética de secagem de cascas da toranja (Citrus paradisi Macf.)

Abstract: The objective of the present study was to characterize physically the grapefruit peel (Citrus paradisi Macf.) and to model the drying of the dehydrated samples at 60, 70, 80 and 90 ºC, evaluating the model adjustments and the drying rates, in their respective temperatures. In natura barks were characterized by water content, total and soluble solids, water activity, ash, pH, total titratable acidity, Ratio and ascorbic acid. The drying kinetics were performed in an air circulation oven, adjusting eleven mathem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Observa-se ainda que, em todos os modelos analisados os valores do parâmetro "k", que representa a constante da taxa de secagem nos modelos empregados, aumenta com a elevação da temperatura e segundo Santos et al (2020) representa o efeito das condições externas de secagem. Os valores do parâmetro de "n" no modelo de Page, não apresenta comportamento específico de acordo com a temperatura variando entre 0,622305 a 1,008967.…”
Section: Resultsunclassified
“…Observa-se ainda que, em todos os modelos analisados os valores do parâmetro "k", que representa a constante da taxa de secagem nos modelos empregados, aumenta com a elevação da temperatura e segundo Santos et al (2020) representa o efeito das condições externas de secagem. Os valores do parâmetro de "n" no modelo de Page, não apresenta comportamento específico de acordo com a temperatura variando entre 0,622305 a 1,008967.…”
Section: Resultsunclassified
“…Satisfactory fits for the same models tested for citron melon peel flours were detected by Santos et al (2020), when studying drying kinetics in grape peels at temperatures of 60, 70, 80 and 90 °C, for which Page model was the one that best fitted to the experimental data obtained, and by Barros et al (2020), who fitted mathematical models to the experimental data of the drying kinetics of kino peels and reported that Page and Approximation of Diffusion models were satisfactory.…”
Section: Results and Discu And Discu And Discu And Discussion Ssion S...mentioning
confidence: 80%
“…It can be observed that all models, except Wang and Singh, showed R 2 values higher than 0.970, indicating that they are adequate for predicting the drying kinetics of the material. Martins et al (2015), Alexandre et al (2019) and Santos et al (2020), stated that R 2 > 0.95 indicates a good representation of the results through mathematical models, but evaluating only this parameter does not constitute a good criterion for selecting nonlinear models, hence requiring joint evaluation of other statistical parameters such as MSD and χ 2 .…”
Section: Results and Discu And Discu And Discu And Discussion Ssion S...mentioning
confidence: 99%
“…A similar behavior was verified by Barbosa and Lobato [48], in studies of the drying kinetics of pineapple slices, observing R 2 values greater than 0.990 when using the Page model in the drying kinetics at temperatures of 60, 65, and 70 • C; and by Olanipekun et al [49], in drying pineapple slices in a convective dryer with an air velocity of 1.5 m/s at temperatures of 50, 60, and 70 • C; also noting that the Page and Two Terms models presented satisfactory adjustments (R 2 > 0.980 and χ 2 ≤ 0.0011). Santos et al [50], when studying the drying of grapefruit peels, reported on the eleven adjusted models, with emphasis on the Page, Logarithmic, Diffusion Approximation, and Midilli models for all temperatures (60, 70, 80, and 90 • C). However, due to its simplicity, they adopted Page's model as the best representation.…”
Section: Resultsmentioning
confidence: 99%
“…Drying is conventionally defined as a process of removing water from agricultural products that involves the simultaneous transfer of heat and mass [13], providing conservation of the material during storage [14]. Through drying kinetics, the data obtained allow us to understand and describe the behavior of the product and its interactions with mass transfer and the drying agent, whose particularities associated with the diversity of materials of biological origin stimulate the interest of researchers in analyzing the drying behavior of the most varied products [15].…”
Section: Introductionmentioning
confidence: 99%